The effects of high-intensity interval training at the anaerobic and psychomotor fatigue thresholds on physiological parameters in young soccer players: a prospective study - Chmura, Paweł; Chmura, Jan; Chodor, Wiktor; Drożdżowski, Adrian; Rokita, Andrzej; Konefał, Marek (Frontiers in Physiology, 2023)
This study aimed to investigate the effects of a 4-week specific high-intensity interval training (HIIT) program performed between the anaerobic threshold (ANT) and the psychomotor fatigue threshold (PFT) on physiological parameters in 14 professional soccer players at the under-17 level. The first and second stages of the research protocol included a treadmill running exercise with increasing load and six 3-min four-versus-four games of soccer with a 3-min break between games. Players then participated in a training microcycle involving three specific HIIT exercises twice per week for 4 weeks, after which they repeated stages one and two, followed by an assessment of changes. The measurement of lactate (LA) determined ANT, whereas the choice reaction time (CRT) indicated PFT among other selected physiological parameters. The repeated-measure analysis of variance (ANOVA) compared mean values for the examined variables using Bonferroni post hoc test. It demonstrated significantly increased maximal oxygen consumption (VO2 max) from 45.9 ± 3.0 to 48.7 ± 2.6 at the ANT and from 49.1 ± 3.4 to 52.0 ± 3.6 on the PFT after 4 weeks of training. A significant increase in the running speed (RS) at both thresholds and heart rate (HR) at the ANT (p ≤ 0.05) was also recorded. Moreover, the players exceeded their intensity of effort during ANT while playing four-versus-four soccer matches, but they did not reach intensity during PFT. In conclusion, the findings of the study demonstrated that both thresholds shifted toward higher loads and the proposed specific HIIT effectively increased the exercise capacity of soccer players.